Nosomorphosis of diseases caused by urogenital infections - A.D. Diudiun; M.Y. Polion; N.N. Polion (Medičnì Perspektivi, 2021)
One of the real threats to the health of the next generation are diseases caused predominantly by sexually transmitted infections (STIs). The frequency of these diseases is constantly increasing among the population of Ukraine and other countries. The aim of our work was to establish the features of the clinical manifestations of diseases caused by urogenital infections (UGI) at the present stage. Under our supervision, there were 577 patients with STIs, 83% of the patients were at the age of the highest socio-economic and sexual activity. A complex of methods for examining the patients included: physical and general clinical studies, laboratory research to identify STIs and conditionally pathogenic microorganisms. A comprehensive complex examination made it possible to identify urogenital chlamydia in 395 (68.5%), trichomoniasis – in 381 (66.03%), ureaplasmosis – in 240 (41.6%), microorganisms associated with bacterial vaginosis – in 80 (13.9%) and urogenital candidiasis – in 75 (13.0%). Monoinfection was diagnosed only in 61 (10.6%) of patients. Among the patients examined, the inflammatory process of the genitourinary organs was supported by two infectious agents in 487 (84.4%), three or more – in 52 (9.0%) of the observed patients. The affection of the urogenital system with STIs occurs with several infectious agents. Clinical manifestations of diseases caused by STIs are asymptomatic or low-symptomatic. The asymptomatic course of diseases caused by STIs leads to a chronic long-term course of the pathological process with the formation of multi-focal lesions and residual phenomena, including proliferative neoplasms.